Healthcare practitioners' experiences of postoperative pain management in lumbar spine surgery care—A qualitative study. Issue 9 (10th March 2020) - Angelini, Eva; Baranto, Adad; Brisby, Helena; Wijk, Helle
Abstract: Aims and objective: To explore and describe healthcare practitioners' experiences of postoperative pain management to patients undergoing planned lumbar spine surgery by identifying the healthcare practitioners' behaviours, attitudes and strategies. Background: Poorly managed postoperative pain continues to cause suffering and prolong hospital care and may affect individual and team practitioners' strategies and attitudes. The impact of these strategies and attitudes needs greater understanding. Design: Descriptive qualitative study. Methods: In‐depth interviews were conducted at a university hospital in Sweden during January–March 2016 with 9 healthcare practitioners (ages: 29–61 years; gender: male 3 and female 6; professions: medical doctor 3, registered nurse 3 and physiotherapist 3; professional experience: 1.5 months to 25 years). The interviews were analysed using Braun and Clarke's thematic analysis. The study adhered to the Consolidated Criteria for Reporting Qualitative Research COREQ. Results: The interviews revealed healthcare practitioners' attitudes and strategies. Three themes were identified: (a) Connecting with the person was recognised as the key component in postoperative pain management; (b) Professionalism: a balancing act, accentuated health care practitioners' duality in being both vulnerable and strong in delicate care situations; and (c) Collaboration: being constantly responsive, the necessity for healthcare practitioners to be constantly responsive to their environment. Conclusions: The findings pinpoint the need for healthcare organisations to build structures enabling practitioners to deliver adequate pain management in acknowledging the practitioners' delicate situation when facing patients in pain. Relevance to clinical practice: Given the global need for postoperative pain management, our findings have international relevance. Preconceived expectations on specific pain need to be depicted and postoperative pain taken seriously to protect the patient as well as the healthcare practitioners.